Tracheostomy-dependent child with temporomandibular ankylosis and severe micrognathia treated by piezosurgery and distraction osteogenesis: Case report - De Castro E Silva, Lucas Martins [UNESP]; Pereira Filho, Valfrido Antonio [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Real Gabrielli, Mário Francisco [UNESP] (Elsevier, 2011)
Ankylosis of the temporomandibular joint in children is one the most difficult and complex conditions managed by oral and maxillofacial surgeons, and often leads to some facial deformity. Distraction osteogenesis of the mandible provides an excellent treatment for mandibular airway obstruction in children who do not respond to conservative measures, and allows for early removal of the tracheostomy. We report the case of a 1-year-old boy with severe micrognathia and temporomandibular ankylosis who was dependent on a tracheostomy; he was treated with piezosurgery and mandibular advancement by distraction osteogenesis. © 2010 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Ankylosis; Distraction osteogenesis; Tracheostomy; arthroplasty; case report; child; childhood disease; clinical examination; computer assisted tomography; disease severity; distraction osteogenesis; human; infant; male; micrognathia; osteotomy; temporomandibular ankylosis; tracheostomy; Arthroplasty; Follow-Up Studies; Humans; Infant; Male; Mandibular Advancement; Micrognathism; Osteogenesis, Distraction; Osteotomy; Piezosurgery; Temporomandibular Joint Disorders